Verifikasi dan Pemetaan Arah Kiblat Bangunan Masjid dan Musola - Fahmi Fatwa Rosyadi Satria Hamdani (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2020)
Qibla's direction of several mosques and musola buildings in Bandung Wetan Sub-District needs to be re-verified. The right direction of the Qibla from the city of Bandung is 295 ° 10 '. The deviation varies due to the condition of the building structure, such as in the alley and following the shape of the land size. It was also caused by the use of tools without calibration and the lack of understanding of the surrounding community about the importance of facing the Qibla when performing prayer. This study aims to analyze the mapping of the direction of the mosque and the musola in Bandung Wetan Sub-District. This study uses a qualitative approach resulting from field observations, with the interactive analysis technique of Miles and Huberman, through the reduction of data generated from the measurement of the Qibla direction, the presentation of essential data on the Qibla direction deviation, and the inference. The results of this study indicate that 70.1% of mosques / musola deviate in the direction of Qibla under 1 degree, while the remaining 29.9% above 1 degree with the furthest deviation by 7°6’